Avaliação da resposta imune e proteção induzidas pela cepa CL-14 de Trypanosoma cruzi, geneticamente modificada para expressar o antígeno A2 de Leishmania L. infantum - Daniel Henrique Doro Pereira (2013)
Leishmaniases comprise a group of infectious diseases caused by protozoan parasites that affect predominantly underdeveloped countries. Among the clinical forms of the disease, visceral leishmaniasis is, certainly, the most severe, being considered the second cause of death, amongst all tropical diseases. Given the severity and complexity of this neglected public health issue, it is necessary to invest in research for vaccines capable of protecting the population under risk. Live attenuated vaccines can simulate the natural course of infection more closely, presenting a rich repertoire of antigens to the hosts immune system, potentially leading to a more potent and durable immunity. In the present study, the Trypanosoma cruzi CL-14 non-virulent strain was transfected with the integrative pROCKNeo plasmid containing a 729bp synthetic A2 gene, which has been previously shown to be immunogenic and protective in different studies. BALB/c mice were immunized intraperitoneally with 107 recombinant parasites through a homologous prime-boost protocol. Sera and splenocytes of mice were collected and tested in ELISA and ELISPOT and checked for anti-A2 antibodies and IFN- production, respectively. The results were compared with the ones obtained for the recombinant protein (rA2) associated with either MPL-A or Alúmen + CpG adjuvants. Mice were then challenged subcutaneously with 107 Leishmania L. infantum promastigotes and the parasite burden of liver and spleen was checked after 30 days. The immunization with the CL-14 A2 construct not only elicited a strong cellular CD4 and CD8 immune response, with high levels of IFN-, but also induced partial protection in BALB/c mice against L. infantum challenge. The difference among these results was significantly statistical when compared to the ones obtained with rA2, despite the use of two distinct adjuvants. Altogether, these results support the A2 antigen as a promising vaccine candidate and suggest that the expression of this protein in the CL-14 non-virulent strain may improve immunogeniticy and protection against visceral leishmaniasis, being an alternative in the search for new vaccines, including the association and test of different antigens and vaccination protocols.